2008
DOI: 10.1519/jsc.0b013e3181635843
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Testosterone and Cortisol Responses in Professional Rugby Players After Four Resistance Exercise Protocols

Abstract: The acute response of free salivary testosterone (T) and cortisol (C) concentrations to four resistance exercise (RE) protocols in 23 elite men rugby players was investigated. We hypothesized that hormonal responses would differ among individuals after four distinct RE protocols: four sets of 10 repetitions (reps) at 70% of 1 repetition maximum (1RM) with 2 minutes' rest between sets (4 x 10-70%); three sets of five reps at 85% 1RM with 3 minutes' rest (3 x 5-85%); five sets of 15 reps at 55% 1RM with 1 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
106
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(121 citation statements)
references
References 20 publications
11
106
4
Order By: Relevance
“…This finding is in contrast to previous work into the endocrine response to maximal speed training. However, an increase in salivary testosterone coupled with a decrease in cortisol has been reported post resistance training (6), and a similar response in serum levels has been reported after a repeated sprint-training session consisting of 4 x 250m sprints with 3 minutes recovery between repetitions (29).…”
Section: Endocrine Response To the Speed Only And Speed And Weights supporting
confidence: 56%
“…This finding is in contrast to previous work into the endocrine response to maximal speed training. However, an increase in salivary testosterone coupled with a decrease in cortisol has been reported post resistance training (6), and a similar response in serum levels has been reported after a repeated sprint-training session consisting of 4 x 250m sprints with 3 minutes recovery between repetitions (29).…”
Section: Endocrine Response To the Speed Only And Speed And Weights supporting
confidence: 56%
“…The cortisol responses observed in the present study were not consistent with previous reports that have shown acute increases in serum cortisol (17,18) or Scortisol (19,20) concentrations after a single bout of a hypertrophy-oriented exercise. Crewther et al (19) suggested that the increase in cortisol concentration is related to the total volume of RE (i.e., number of sets x external load).…”
Section: Discussioncontrasting
confidence: 99%
“…There were no similarities in baseline characteristics (eg, high power output) between the responders and nonresponders to explain the variability in the change of performance to the same training program. One mechanism proposed by Beaven and colleagues 32 suggested that players have differing individual hormonal responses to a single resistance training session. In addition, when players trained using resistance training that elicited the greatest testosterone response, significant improvements in strength occurred.…”
Section: Discussionmentioning
confidence: 99%